Interactive Learning Media: Bilingual Science Flipbook For Solar System - Amira Taufik; Arif Widagdo (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to develop interactive media flipbook bilingual solar system material, describe the feasibility and effectiveness of interactive media, and familiarize English vocabulary to students. The research method used is the research and development method with the ADDIE development model. The subjects of this research were 6th grade students of SD N Kandri 01 Semarang City conducted from April to May 2024. The methods used in this research are interview, observation,  questionnaire, test, and documentation. The instruments used were interview guides, documentation, needs and response questionnaires, pretest and posttest questions, and validation sheets. Data analysis was done with a normality test, t-test, and n-gain test. The results of this study show that bilingual flipbook media is feasible to use with a percentage of feasibility from media validators 96%, material validators 91%, and language validators 95%. The result of the small-scale normality test is 0.068, and the large-scale 0.035 means that the data distribution is normal. The results of the small-scale n-gain test were 0.511, a large scale of 0.549, it included a moderate category. The conclusion of this study is that bilingual flipbook media is feasible and effective to use as a medium for learning science in class